Marketing Communication Strategy Planning to Increase Brand Awareness of The Traditional Beverage Brand “Loloh” - verene Ysabell Lietania; Azka Muzakiah (CV. Syntax Corporation Indonesia, 2023)
Throughout the history of mankind, human beings are prone to suffering by the emergence of diseases and illnesses. To keep human civilization intact and functioning, people from different cultural backgrounds have discovered methods to heal and treat themselves to prevent upcoming diseases bestowed on the human race by utilizing medicinal plants, also known as herbal medicine. The demand for herbal medicine skyrocketed during the COVID-19 pandemic, as public awareness of the significance of improving immunity grew. Loloh being a brand in the F&B industry that sells traditional herbal beverages popularly known in Indonesia as jamu had encountered difficulties which resulted in its lack of awareness and online presence. Therefore, the aim of this marketing communication planning project is to increase the awareness for the brand by implementing online promotional strategies and content marketing in social medias like Instagram and Facebook. The execution stage of this project will use the SOSTAC method by Smith & Chaffey (2017). The results will be evaluated through analytics and sales results after the strategies has been implemented throughout.